Understanding the Interrelationship Between Country of Origin, Ethnocentrism, and Purchase Intentions - Kaur, Japneet; Kaur, Prabhjot (Prabandhan: Indian Journal of Management, 2015)
This paper has investigated the effect of consumer ethnocentrism (CE) and country of origin (COO) on purchase intentions (PI). Increasing popularity of foreign brands among Indian consumers over the last two decades created a need for this study. An empirical analysis was conducted on 100 Indian consumers residing in Tricity (Chandigarh - Mohali - Panchkula) to explore the relationship between various factors responsible for foreign brand purchase. Results revealed a negative relationship between consumer ethnocentrism and purchase intentions of foreign brands. Furthermore, significant differences were found in consumer ethnocentric tendencies across demographic variables.